Técnicas de análisis en cestería de los contextos funerarios del sitio arqueológico La Pampa - Valle Camaná, durante el Horizonte Medio - Avalos Jara, Tania Katherine (2022)
This research focuses on the analysis of basketry objects from the funerary contexts of the archaeological site La Pampa, through the study of construction techniques, which were made of vegetable fiber, thus getting to know the different construction technologies and the activities carried out by the ancient inhabitants of Camana. Therefore, it was necessary to classify according to the number of elements that are composed, obtaining four categories, which results were: 1) A set of elements with the cordage technique (little ropes and ropes) and braiding technique (weaver's baskets, envelope bag and bonnet); 2) Two or more sets of elements with the interlacing technique (quadrangular bag, rectangular bag, trapezoid bag and elongated bag), 3) Two individual elements that are based on the spiraling technique (plates) and 4) This last category was called “others”, that are objects which technique have not been able to identify given their poor state of preservation. In conclusion, with this research I led that basketry found in funerary contexts is being evidenced as a specialized cultural tradition of domestic and ritual function. This activity reflects the knowledge of the raw material used and the processing techniques, which have been transmitted through time and at the same time shows innovation in several production techniques in basket weaving and mastery in the knowledge of the vegetable fibers used by the pre-Hispanic settlers of Camana.